Comparative Study of Implantable Collamer Lens Implantation in Treating Four Degrees of Myopia: Six-Month Observation of Visual Results, Higher-Order Aberrations, and Amplitude of Accommodation. (2nd July 2020) - Wan, Ting; Yin, Houfa; Wu, Zhiyi; Yang, Yabo
ABSTRACT: Purpose: To compare the visual and refractive outcomes, higher-order aberrations (HOAs), and amplitude of accommodation (AA) after implantable collamer lens (ICL) model V4c implantation in four degrees of myopia. Methods: One hundred and thirty-seven myopic eyes (137 patients) undergoing ICL implantation were included and divided into four groups: Group 1 with spherical equivalent (SE) ≤−6.0D, Group 2 with SE from −6.13D to −9.0D, Group 3 with SE from −9.13D to −12.0D, and Group 4 with SE from −12.13D to −18.0D. The postoperative visits were scheduled at 1 day, 1 week, 1 month, 3 months, and 6 months. Visual and refractive outcomes, HOAs and AA were observed and compared. Results: At 6 months postoperatively, the uncorrected distance visual acuity (UDVA) in Group 4 was worse than the values in the other groups (all p < .05). Meanwhile, Group 4 had more eyes with corrected distance visual acuity (CDVA) improvement than the other groups. Furthermore, 96%, 100%, 100%, and 81% of eyes had an SE within ±0.5D in Group 1, Group 2, Group 3, and Group 4 ( p < .05 between Group 4 and the other groups), respectively. The postoperative UDVA and SE remained stable in all groups. No significant change in total HOAs was found between preoperative and postoperative values for each group. However, quatrefoil increased in each group, whereas trefoil was induced in all groups except for Group 1. Negative spherical aberration was induced in Group 3 and Group 4. AA significantly decreased 1 week postoperatively and gradually improved in each group. Although AA improved to the preoperative level in Group 1 at 3 months postoperatively, it was still lower than the preoperative level in the other groups. Conclusions: In treating different degrees of myopia with ICL implantation, differences were observed in terms of CDVA improvement, SE predictability, HOAs induction, and accommodation recovery.